Uterine atony risk factor after vaginal delivery in a tertiary hospital in Antananarivo, Madagascar - A. Ratsiatosika, Tanjona; Romuald, Randriamahavonjy; A. Lantonirina, Rainibarijaona; I. A., Housni; A. Martial, Rakotonirina; Ismael Mhoudine, Said; Ando-Miora, Rakotonirina; H. Rakotovao, Andrianampanalinarivo (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Postpartum hemorrhage is the leading cause of maternal death in developing countries. Uterine atony is the cause in 80% of cases. Through this study, we want to determine risk factors for uterine atony after vaginal delivery route with oxytocin-mediated delivery. Methods: This is a retrospective case-control study ranging from January 1st 2017 to June 31st 2018 at the Befelatanana University Hospital Centre of Gynecology-Obstetrics. The cases consisted of patients who had spontaneous vaginal delivery in the centre and had uterine atony. Authors studied maternal, obstetrical, neonatal parameters. Authors used the R software for the statistical analysis of the results. Results: We found 40 cases of uterine atony out of 5421 deliveries with a prevalence of 0,73%. The average age was 27.73 years old±6.46 years old (p=0.113). The average parity was 2.67±1.62 (p=0.22). The total duration of labor was 6.88±2.95 hours (p=0.0187). The average duration of rupture of the membrane was 5.80±11.90 hours (0.003376). We found as risk factor of uterine atony the increase in oxytocin infusion rate during labor (OR=18.67, 95% CI 2.21-157.57), the artificial rupture of membranes (OR=5, 27, 95% CI 2.11-13.19), artificial induction of labor (OR=7.08, 95% CI 2.06-24.28) and labor over six hours (OR=2.53, 95% CI) % 1.18-5.47). In univariate analysis, premature delivery and a hypotrophic fetus were a factor risk of uterine atony (OR=3.07, 95% CI 1.27-7.44 and OR=3.43 95% CI 1.48-8.09 respectively) but this risk is not statistically significant in multivariate analysis with logistic regression (OR=1.27, 95% CI 0.40-3.84 and OR=2.19 95% CI 0.77-6.22). The main treatment was uterotonic drug use (72.5%). Authors identified seven cases of haemostasis hysterectomy and two cases of maternal death. Conclusions: Present study confirms risk factors for uterine atony already known as prolonged labor and increased oxytocic infusion rate. Unrecognized factors have been identified as a risk factor for uterine atony such as the duration of rupture of the membranes and artificial rupture of the membranes. A minimal inflammation hypothesis that reduces susceptibility to oxytocin may explain this association. Knowing these factors would reduce the occurrence of uterine atony to reduce maternal mortality.